Analysis Of The Intensity Of Gadget Use By Class Xi Culianry Students In Pastry And Bakery Subjects At Smkn 9 Padang - Armel, Bunga Melati; Siregar, Juliana; Yulastri, Asmar; Andriani, Cici (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research is motivated by the emergence of positive and negative impacts in the use of gadgets in the learning process. Apart from the positive impact, the use of gadgets in the learning process has a negative impact, namely disrupting concentration when studying, students being more individual or closed, preferring to be alone with gadgets, which can reduce their ability to socialize in the school environment. This research aims to describe the intensity of gadget use and the learning outcomes of class XI Culinary students in pastry and bakery subjects. This research method is a quantitative correlational approach. The population in this study was class XI Culinary students with a total of 134 students. The research sample consisted of 57 people with the sampling technique being simple random sampling. The data collection technique was carried out using a questionnaire using a Likert scale which has been tested for validation and reliability. Data analysis uses descriptive analysis and correlational analysis.